Pengembangan E-LKPD Berbasis Media Canva Untuk Meningkatkan Kemampuan Berpikir Kritis Pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas V Sekolah Dasar - Aqilah Salsabila; Jamaluddin Arifin; Muhajir Muhajir (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the characteristics of LKPD used in schools, design a conceptual design of Canva-based E-LKPD, and test the level of validity, practicality, and effectiveness of Canva-based E-LKPD in improving the critical thinking skills of fifth-grade students in the Pancasila Education subject. The study was conducted at SDN 53 Banyorang using the Research and Development (R&D) method through the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was carried out using validation instruments from material experts and media experts, observation sheets, teacher response questionnaires, student response questionnaires, and critical thinking ability tests. The results of the study showed that the resulting product was a Canva-based E-LKPD on the material